Incidence and Clinical Impact of Stent Fracture After the Nobori Biolimus‐Eluting Stent Implantation. Issue 2 (20th March 2014) - Kuramitsu, Shoichi; Iwabuchi, Masashi; Yokoi, Hiroyoshi; Domei, Takenori; Sonoda, Shinjo; Hiromasa, Takashi; Morinaga, Takashi; Kobayashi, Yohei; Ohe, Kensuke; Goya, Kaoru; Yamaji, Kyohei; Hyodo, Makoto; et al.
Abstract : Background: Stent fracture (SF) after drug‐eluting stent implantation has become an important concern. The aim of this study was to assess the incidence, predictors, and clinical impact of SF after biolimus‐eluting stent. Methods and Results: A total of 1026 patients with 1407 lesions undergoing the Nobori biolimus‐eluting stent implantation and follow‐up angiography within 9 months after index procedure were analyzed. SF was defined as complete or partial separation of the stent, as assessed by using plain fluoroscopy, intravascular ultrasound, or optical coherence tomography during the follow‐up. We assessed the rate of SF and the cumulative incidence of clinically driven target lesion revascularization and definite stent thrombosis within 9 months. SF was observed in 58 (4.1%) of 1407 lesions and 57 (5.5%) of 1026 patients. Lesions with hinge motion (OR 8.90, 95% CI 3.84 to 20.6, P <0.001), tortuosity (OR 4.16, 95% CI 1.75 to 9.88, P =0.001), and overlapping stents (OR 2.41, 95% CI 0.95 to 6.10, P =0.06) were predictors of SF. Cumulative incidence of clinically driven target lesion revascularization within 9 months was numerically higher in the SF group than that in the non‐SF group (12.0% versus 1.0%). Cumulative incidence of definite stent thrombosis within 9 months tended to be higher in the SF group than that in the non‐SF group (1.7% versus 0.5%). Conclusions: SF after biolimus‐eluting stent occurs in 4.1% of lesions and appears to be associated with clinically driven target lesion revascularization.